Cutaneous toxicities in patients with melanoma receiving checkpoint inhibitor therapy: a retrospective review. The experience of a single large specialist institution. (1st March 2021) - Edwards, C. L.; Comito, F.; Agraso Busto, S.; Harland, C.; Turajlic, S.; Larkin, J.; Heelan, K.; Fearfield, L.
Summary: Checkpoint inhibitor (CPI) therapy has significantly improved overall survival for metastatic melanoma, and is now approved for use in the adjuvant setting. Modulating the immune system is recognized to cause cutaneous immune‐related adverse events (irAEs). We conducted a retrospective observational cohort study of adult patients with melanoma at our tertiary referral centre, who received CPI therapy from 2006 to March 2018. This is the single largest study of cutaneous irAEs occurring on CPI therapy in patients with melanoma to date and encompasses 12 years. The results showed that cutaneous toxicity occurs in 24% of patients but is generally manageable, with < 5% patients discontinuing treatment.